In situ Preservation Solutions for Deposited Iron Age Human Bones in Alken Enge, Denmark. (2nd July 2016) - Tjelldén, Anna K.E.; Matthiesen, Henning; Petersen, Lucia M.M.; Emil Søe, Niels; Kristiansen, Søren M.
Abstract : The rich mass deposition of Iron Age human bone material from the Danish site, Alken Enge, is extraordinary not only from an archaeological perspective but also from a preservation point of view. The main find is situated in a waterlogged, anoxic environment which provides excellent preservation conditions and therefore enables in situ preservation of the human bones. However, major differences in local environmental conditions challenge an in situ preservation of the entire site area as parts of the bone material presently deteriorate. In this paper, a multi-proxy environmental monitoring approach is used to document threats and to suggest the best preservation solution for the archaeological finds, whether in or ex situ .